Tryptic digestion coupled with ambient DESI and LESA mass spectrometry enables identification of skeletal muscle proteins in mixtures and distinguishes between beef, pork, horse, chicken and turkey meat - Montowska, Magdalena; Rao, Wei; Alexander, Morgan R.; Tucker, Gregory A.; Barrett, David A. (American Chemical Society, 2014)
The use of ambient desorption electrospray ionization (DESI-MS) mass spectrometry and liquid extraction surface analysis mass spectrometry (LESA-MS) is explored for the first time to analyse skeletal muscle proteins obtained from mixture of standard proteins and raw meat. Single proteins and mixtures of up to five proteins (myoglobin, troponin C, actin, BSA, tropomyosin) were deposited onto a polymer surface, followed by in-situ tryptic digestion and comparative analysis using DESI-MS and LESA-MS using tandem electrospray MS. Peptide peaks specific to individual proteins were readily distinguishable with good signal-to-noise ratio in the five-component mixture. LESA-MS gave a more stable analysis and greater sensitivity compared with DESI-MS. Meat tryptic digests were subjected to peptidomics analysis by DESI-MS and LESA-MS. Bovine, horse, pig, chicken and turkey muscle digests were clearly discriminated using multivariate data analysis (MVA) of the peptidomic datasets. The most abundant skeletal muscle proteins were identified and correctly classified according to the species following MS/MS analysis. The study shows, for the first time, that ambient ionization techniques such as DESI-MS and LESA-MS have great potential for species-specific analysis and differentiation of skeletal muscle proteins by direct surface desorption.